التسيير النسوي كنموذج لقيادة الابتكار حالة مؤسسة:المشروبات الغازية والمياه المعدنية القولية بالمنيعة ولاية غرداية - ربوح, أم الخير; محسن, زوبيدة; بن قرينة, محمد حمزة (جامعة الوادي University of Eloued, 2018)
نهدف من خلال هذا العمل إلى إبراز دور التسيير النسوي في المؤسسات الجزائرية كنموذج لقيادة الابتكار، وذلك من ناحية نشاط المرأة في أداء العمل المقاولي للأعمال والذي يسمح لها بتحقيق ميزة تنافسية، وبالتالي فإن ذلك يعد دافع أساسي للقيادة الابتكار، والذي تتمكن المرأة من خلاله التأثير على سلوك الموظفين وتنسيق جهودهم لتحقيق أهداف معينة من بينها تحقيق خطط المؤسسة وتصوراتها المستقبلية، ومن خلال هذا الطرح قمنا بصياغة الإشكالية التالية: هل يمكن اعتبار التسيير النسوي كنموذج لقيادة الابتكار في المؤسسات الجزائرية؟ Us aim of this work to highlight the role of the Management feminist in theAlgerian institutions as a model to lead innovation, in terms of women's activity in the entrepreneurial work of business performance which allows it to achieve a competitive advantage, so this is a obligate motivation for driving innovation, which women can through which to influence the behavior of the officer and coordinate their efforts to achieve certain aims, including the achievement of the organization's plans and perceptions of the future, and through this proposal, we have formulated the following problem :Can we consider the management feminist model for driving innovation in the Algerian institutions?
مقال
Keywords: تسيير نسوي، قيادة الابتكار، امرأة مقاولة، ميزة تنافسية مستدامة; management feminist, driving innovation , woman entrepreneurs,sustainable competitive advantage